Overexpression of RAPGEF3 enhances the therapeutic effect of dezocine in treatment of neuropathic pain - Xue Liu; Li Song; Xiaojun Ma; Yong Liu; Hui Huang; Yongsheng Xu; Wei Yan (Genetics and Molecular Biology, 2021)
Abstract Pain is a significant problem worldwide that affects the quality of life of patients. Dezocine is a non-addictive analgesic drug with kappa-opioid antagonist activity and has been successfully used to alleviate of postoperative pain. In addition, dezocine has an analgesic effect similar to that of morphine, alleviating moderate to severe pain. Rap guanine nucleotide exchange factor 3 (RAPGEF3) is a guanine nucleotide exchange factor for GTPases Rap1 and Rap2, which could enhance the activity of Rap1 to promote cell adhesion and axon regeneration, as well as promote neurite extension by interacting with nerve growth factors. Here, we first observed that overexpression of RAPGEF3 increased cell viability, as shown by a CCK-8 assay, and recovered brain function in rats. The expression of inflammation-related factors at the mRNA level was detected using qPCR, and the concentration of these factors in a cultured cell medium and rat serum samples were decreased as shown by ELISA after RAPGEF3 overexpression. Through western blotting, we further found that pro-inflammatory proteins were decreased, and these effects might be mediated by inhibition of the Ras/p-38 MAPK signaling pathway. Taken together, we speculated that RAPGEF3overexpression enhances the therapeutic effect of dezocine on neuropathic pain by inhibiting the inflammatory response through inhibition of the Ras/p-38 MAPK signaling pathway.